Unexpected convergence: the Huntington/Fukuyama debate - Georghiou, Costa (University of the Free State, 2014)
Two theories that have drawn particular attention in international politics, especially to explain global post-Cold War developments, are those of Huntington’s (1993) Clash of civilizations and Fukuyama’s (1992) The end of history and the last man. There is a great deal of literature on the mutually contradictory views of these two authors; however, the literature hardly mentions the actual unexpected areas of convergence between these two theorists, which this article aims to draw out. Four pertinent questions addressed by Huntington and Fukuyama are considered, namely the universality of Western civilisation; the role of the state; modernisation versus Westernisation, and worldwide acceptance or rejection of liberal democracy, as they relate specifically to the central aim of this article. It is precisely because of their differences, that these two distinct theories are now presenting themselves as alternatives in international relations: one can either see the world to be developing toward its final liberal democratic destination, or, alternatively on a multi-polar, civilisation-divergent course. As the search for a single paradigm within debates on international relations continues, a convergence between two major theories, such as these, is important, as they provide one more step toward consensus between opposing views on international political developments.
Keywords: Clash of civilizations (1993); Huntington, Samuel P.; The end of history and the last man (1992); Fukuyama, Francis; Western civilisation; Westernisation; Modernisation